Heterodimeric Radiotracer Targeting PSMA and GRPR for Imaging of Prostate Cancer—Optimization of the Affinity towards PSMA by Linker Modification in Murine Model - Lundmark F. Fanny; Abouzayed A. Ayman; Mitran B. Bogdan; Rinne S. S. Sara; Varasteh Z. Zohreh; Larhed M. Mats; Tolmachev V. M. Vladimir Maksimilianovich; Rosenstrom U. Ulrika; Orlova A. M. Anna Markovna (2020, 2020)
Title screen